IMPLEMENTATION OF VILLAGE GOVERNMENT POLICY ON THE ESTABLISHMENT AND MANAGEMENT OF VILLAGE-OWNED BUSINESS ENTITIES IN BATUKARAS VILLAGE CIJULANG DISTRICT PANGANDARAN DISTRICT - Adi Suryadi; Aan Anwar Sihabudin; Asep Nurwanda (Faculty of Social And Political Science Universitas Galuh, 2021)
This research is based on the problem that the implementation of village government policies regarding the formation and management of village-owned enterprises in Batukaras Village, Cijulang District, Pangandaran Regency is still not optimal, this happens because there is no good communication between the village government and the community so that the level of participation of the village community Batukaras in participating in developing the BUMDes business of Batukaras Village Partners is still low, Lack of socialization carried out by the village government and Lack of human resources for BUMDes managers. The research method used in this research is descriptive qualitative by conducting observations and interviews with 4 (four) informants, namely 1 (one) Head of Batukaras Village, Staff Head of Service, Head of BUMDes Mitra Batukaras Village, and Treasurer of BUMDes. The results of this study indicate that the implementation of village government policies regarding the establishment and management of village-owned enterprises in Batukaras Village, Cijulang District, Pangandaran Regency as a whole from various activities carried out has been going well but still not optimal. This can be seen from the lack of socialization that was carried out and also the BUMDes managers or Human Resources who did not understand the functions, and the communication that was carried out did not go well, the direction and policies provided did not motivate BUMDes implementers.